Merancang Perangkat Flipped Classroom - Hidayat, Asep; Munggaran, Nantia Rena Dewi; Herdhiana, Ria (Jurnal Pengabdian Tri Bhakti, 2023)
The problem for teachers with online learning is that they have difficulty controlling learning, while from the students' point of view they have to spend time doing homework with the help of parents or other family members who do not necessarily master the material. To deal with these problems, learning with the Flipped Classroom model can be used. Flipped Classroom is a type of mixed learning in which students independently study material at home or preclass, then practice working on it or practice together with the teacher at school. This service aims to (1) improve the knowledge and skills of teachers in choosing learning videos and making learning videos, either in the form of video tutorials, short films or VPT (Voice Over Power Point) within the TPACK (Technological, Pedagogical, and Content Knowledge) framework to be presented. at preclass; and (2) improving the knowledge and skills of teachers in designing Flipped Classroom learning activities in the form of a one-page lesson plan. Service partners are teachers at MTs. Miftahulfalah Bandung. The service is carried out by training methods using the Flipped Classroom model, where material is given through Google Classroom one week before the mentoring; then assistance in making learning videos and lesson plans is carried out together in class. The results show an increase in teacher knowledge and skills in making learning videos and designing Flipped Classroom learning models.